Structural and seismic vulnerability assessment of the Santa Maria Assunta Cathedral in Catanzaro (Italy): classical and advanced approaches for the analysis of local and global failure mechanisms (Fracture and Structural Integrity, 2022)
The evaluation of the seismic vulnerability of existing buildings is becoming very significant nowadays, especially for ancient masonry structures, that represent the cultural and historical heritage of our countries. In this research, the Cathedral of Santa Maria Assunta in Catanzaro (Italy) is analyzed to evaluate its structural response. The main physical properties of the constituent materials were deduced from an extensive diagnostic campaign, while the structural geometry and the construction details were derived from an accurate 3D laser scanner survey. A global dynamic analysis, based on the design response spectrum, is performed on a finite element model for studying the seismic response of the structure. Moreover, a local analysis is conducted to evaluate the safety factors corresponding to potential failure mechanisms along preassigned failure surfaces. Furthermore, pushover analyses are performed on macro-elements, properly extracted from the whole structure and with an independent behavior with regard to seismic actions. A novel model based on inter-element fracture approach is used for the material nonlinearity and its results are compared with a well-known classical damage model in order to point out the capability of the method. Finally, the results obtained with the three different models are compared in terms of seismic vulnerability indicators.
Keywords: Historical masonry structures; Pushover analysis; Cohesive finite element models; Damage models; Seismic vulnerability assessment